2008
DOI: 10.1016/j.molcel.2008.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of RNA Polymerase Assembly Dynamics in Transcriptional Regulation

Abstract: The interaction of transcription factors with target genes is highly dynamic. Whether the dynamic nature of these interactions is merely an intrinsic property of transcription factors or serves a regulatory role is unknown. Here we have used single-cell fluorescence imaging combined with computational modeling and chromatin immunoprecipitation to analyze transcription complex dynamics in gene regulation during the cell cycle in living cells. We demonstrate a link between the dynamics of RNA polymerase I (RNA P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
3
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 46 publications
(91 reference statements)
4
80
3
2
Order By: Relevance
“…An FHDC implies that changes in factor concentration act like a rheostat to give a continuum of responses (2,4,36,37), which suggests that gene expression by steroid receptors during development, differentiation, and homeostasis employs differential control, as seen with other transcription factors and morphogens (38)(39)(40)(41). This rheostat model is fully compatible with the many observations that the binding of steroid receptors and transcription factors is rapid and readily reversible (12,13,42). Indeed, the rapid binding of steroid receptors is a consequence of FHDC and a prediction of our theoretical framework.…”
Section: Discussionsupporting
confidence: 64%
“…An FHDC implies that changes in factor concentration act like a rheostat to give a continuum of responses (2,4,36,37), which suggests that gene expression by steroid receptors during development, differentiation, and homeostasis employs differential control, as seen with other transcription factors and morphogens (38)(39)(40)(41). This rheostat model is fully compatible with the many observations that the binding of steroid receptors and transcription factors is rapid and readily reversible (12,13,42). Indeed, the rapid binding of steroid receptors is a consequence of FHDC and a prediction of our theoretical framework.…”
Section: Discussionsupporting
confidence: 64%
“…Previous FRAP experiments have shown that the Pol I machinery dynamically assembles at the rDNA promoter, individual Pol I subunits, or subcomplexes interacting with rDNA in a stochastic manner (10,13). If Ser170/172 phosphorylation promotes dissociation of TIF-IA from Pol I, the nucleolar residence time of GFPtagged TIF-IA should be lower than that of TIF-IAS170/172A and TIF-IA/RPA43.…”
Section: Resultsmentioning
confidence: 99%
“…Stochastic assembly of transcription factors at their target sites has been described in several systems (14). For HMGB1 and GR, Agresti et al argue that in living cells the stochastic assembly of rapidly moving chromatin binding protein at specific binding sites mutually reinforces their chromatin interactions (1).…”
Section: Discussionmentioning
confidence: 99%